RELEVANT ISSUES OF THE DEVELOPMENT OF CONTINUING ECONOMIC EDUCATION AT THE PRESENT STAGE - Taranenko, Natalia; Okorokova, Olga; Nikolaevna Korotun, Olga; Sergeevich , Ilya; Chekkueva, Laura; Nikolaevna , Evgenia (Revista Inclusiones, 2020)
The article is aimed at the study of the development of continuing economic education in Russia at the present stage as an element of the system of continuing professional education. The conducted research is based on the problem principle that implies interdisciplinary and multidisciplinary study. Education for adults is considered as one of the theoretical and practical problems. A brief retrospective analysis of the formation of andragogy as a science generalizing the practice of education for adults helping them acquire general and professional knowledge is provided. The article deals with the system of continuing professional education in Russia at the present stage and its specifics: the implementation of professional standards in developing programs of continuing professional education, the opportunities for their use outside of educational institutions, the introduction of automated information system for collecting, analyzing, and providing information about organizing continuing professional education and training in the Russian Federation and about the federal register of certificates of education and training.